2020
DOI: 10.1002/14651858.cd001168.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating oral lichen planus: corticosteroid therapies

Abstract: Background Oral lichen planus (OLP) is a relatively common chronic T cell-mediated disease, which can cause significant pain, particularly in its erosive or ulcerative forms. As pain is the indication for treatment of OLP, pain resolution is the primary outcome for this review. This review is an update of a version last published in 2011, but focuses on the evidence for corticosteroid treatment only. A second review considering non-corticosteroid treatments is in progress. Objectives To assess the e ects and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 108 publications
3
100
0
Order By: Relevance
“…A recent Cochrane review [ 21 ] quoted that the impact of pain on physical, emotional, and social functions required multidimensional qualitative tools and health-related quality of life instruments that are uncommonly used in OLP trials. Due to the chronic nature of OLP and the impact of this condition on quality of life, the use of patient-reported outcome measures in assessing the treatment of chronic oral mucosal diseases is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review [ 21 ] quoted that the impact of pain on physical, emotional, and social functions required multidimensional qualitative tools and health-related quality of life instruments that are uncommonly used in OLP trials. Due to the chronic nature of OLP and the impact of this condition on quality of life, the use of patient-reported outcome measures in assessing the treatment of chronic oral mucosal diseases is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…As topical steroids are first line treatment of OLP, recent placebo controlled trials on different types of steroids like clobetasol propionate 0.05% mixed with 4% hydroxyethyl cellulose gel (Lodi, Manfredi, Mercadante, Murphy, & Carrozzo, 2020), triamcinolone paste and tacrolimus ointment (Lodi et al, 2020) showed significant reduction of clinical signs of OLP against orabase and 4% hydroxyethyl cellulose gel alone (considered as placebo) in symptomatic OLP patients (Lodi et al, 2020). Our results are comparable to these studies, but unlike these studies, the drug effect durability of MMF patch on OLP is not evaluated and needs more investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Lichen planus (LP) is a common inflammatory disease of the skin, mucous membranes, nail, and hair follicles (Nazemi, Esmaeli, Sedaghat, & Mostafa, 2006), in which autoreactive T lymphocytes are directed against basal layer antigens. The lesions can vary from a mild inflammation to destruction of the epithelium with painful wounds (Glick, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to an updated review about OLP treatment, the aims of therapeutic management are eliminating painful symptoms, promoting healing of erosive lesions, reducing the risk of malignant transformation, and prolongating symptom free periods [15]. For erosive OLP, corticosteroids were recommended as first-line treatment in consensus guidelines [15,16]. However, systemic or topical application of corticosteroids present various adverse effects, containing oral candidiasis, a smarting sensation in the mouth, gingival tenderness, insomnia, mood swings, fatigue, and water retention [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…For erosive OLP, corticosteroids were recommended as first-line treatment in consensus guidelines [15,16]. However, systemic or topical application of corticosteroids present various adverse effects, containing oral candidiasis, a smarting sensation in the mouth, gingival tenderness, insomnia, mood swings, fatigue, and water retention [16][17][18]. Moreover, there is no definitive protocol of corticosteroid therapy for children aged three.…”
Section: Discussionmentioning
confidence: 99%